Job stress with supervisor's social support as a determinant of work intrusion on family conflict - Azman Ismail; Fara Farihana Suhaimi; Rizal Abu Bakar; Syed Shah Alam (Journal of Industrial Engineering and Management (JIEM), 2013)
Purpose: The primary objective of this study is to examine the influence of supervisor's social support in the correlation between job stress and work intrusion on family conflict.Design/methodology/approach: A survey method was employed to gather survey questionnaires from academic staff in a Malaysian government university in Borneo. Findings: The outcomes of SmartPLS path model showed three major findings: first, supervisor's social support does act as an important moderating variable in the relationship between role ambiguity and work intrusion on family conflict. Second, supervisor's social support does not act as an important moderating variable in the relationship between role conflict and work intrusion on family conflict. Third, supervisor's social support does not act as an important moderating variable in the relationship between role overload and work intrusion on family conflict. In sum, supervisor's social support does act as a partial moderating variable in the hypothesized model. Practical implications: The findings of this study can be used as guidelines by management to overcome job stress problems through updating the content and methods of stress management training program, strengthening work groups and group cohesiveness in executing job, improving work-life balance programs to reduce the employee physiological and psychological stresses, revisiting the existing job designs based on the qualifications and expectations of individual employees, and revising compensation and benefits policies and procedures to cover stress-related disorder diseases, and activating internal employee assistance programme in order to help employees and their families with problems arising from both work-related and external resources. If these suggestions are given highly attention this may increase the capability of employees to enhance the performance of institutions of higher learning. Originality/value: The role of supervisor's social support in influencing the effect of job stress on family conflict is commonly investigated in Western countries, but it has not been thoroughly studied in the context of this study.
Keywords: 650; job stress; supervisor's social support; work intrusion on family conflict